Actividad física recreativa: incidencia en el desarrollo emocional de adultos mayores de 60 a 80 años en la Ciudadela Loma Grande del cantón Ventanas - Leon Herrera, Peter John (2023)
Recreational physical activity and the emotional development of the elderly maintain a relationship in terms of the benefits generated by these physical practices, and the emotional difficulties that the elderly present at these ages, considering the advantages of one variable and the problems of the other. an important link is created. Therefore, the present study had the purpose of determining the incidence of recreational physical activity in the emotional development of adults aged 60 to 80 years in the Loma Grande citadel of the Ventanas canton. A qualitative, descriptive, non-experimental, cross-sectional research design was used. In the same way, an emotional intelligence test proposed by Markos (2007) and a survey were applied to find out the degree of satisfaction towards recreational physical activity and an interview with a selected non-probabilistic sample of 20 older adults from the Loma Grande citadel of the canton. Ventanas (8 women and 12 men), for subsequent analysis in terms of recreational physical activity and emotional development of the object of study through documentary review and field research respectively. Among the results, it was shown that 80% of the older adults under study present deficient emotional behavior, for which it is intended to establish the proposal of a plan of recreational physical activities to improve the emotional development of the older adults of the town before mentioned.